2015
DOI: 10.1080/13674676.2015.1042851
|View full text |Cite
|
Sign up to set email alerts
|

Family size and psychological functioning in the Orthodox Jewish community

Abstract: Caring for children is a known psychosocial stressor; however, its effects on psychological functioning may have substantial cross-cultural variance. We explored relationships between family size and a variety of psychological outcomes among Orthodox Jews in four separate studies: (1) an international treatment-seeking sample (n = 82), (2) a community sample from Canada (n = 226), (3) an out-patient clinical sample from greater New York (n = 82), and (4) a large dyadic sample of Israeli couples (n = 789). Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…A third interesting finding is that while family size was associated with elevated work stress, it was also associated with enjoying life and finding positive impact of the pandemic period. Though prior studies have reported generally mixed findings (Angrist et al 2010 ), our results add to the body of work suggesting that the resilience-promoting properties of large families within the Orthodox community may outweigh related stressors (e.g., Pirutinsky et al 2015 ).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…A third interesting finding is that while family size was associated with elevated work stress, it was also associated with enjoying life and finding positive impact of the pandemic period. Though prior studies have reported generally mixed findings (Angrist et al 2010 ), our results add to the body of work suggesting that the resilience-promoting properties of large families within the Orthodox community may outweigh related stressors (e.g., Pirutinsky et al 2015 ).…”
Section: Discussionsupporting
confidence: 47%
“…In fact, social support proffered by faith communities is generally an important mediator of the association between religion and health—both mental (Koenig 2018 ) and physical (Koenig et al 2012 ), and Orthodox Jews typically gather for communal prayer three times daily and gather regularly for communal events, religious holidays, life cycle occasions, and religious study. In addition, more traditional Orthodox communities may be particularly affected as they are composed of large families (Pirutinsky et al 2015 ), many of whom experience low socioeconomic status (Pearson and Geronimus 2011 ) and have limited access to technology (Hack 2007 ), which has become uniquely important to daily life under social distancing conditions (Ho et al 2020 ). Finally, beyond the direct impact on Jews’ physical and mental health, conspiracy theories about COVID-19 have targeted Jews, echoing old libels related to past pandemics, and anti-Semitic incidents have increased 18% since the outbreak (Kantor Center 2020 ; Heller 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, stay-at-home restrictions may have been particularly stressful for Orthodox Jews since their culture is collective, communal, and familial (Heilman 2000 ). In addition, more traditional Hasidic or Haredi communities tend to be composed of large families (Pirutinsky et al 2015 ) of low socioeconomic status (Pearson and Geronimus 2011 ). The community’s resistance to smartphones and Internet access has posed unique challenges during the pandemic due to the widespread reliance on such technologies in the face of social distancing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lesser attention to religious minority persons and families is unfortunate, given the often unique challenges and struggles religious minorities face in both public and private spheres-including, for example, the workplace challenges of Muslims (Alghafli, Marks, Hatch, & Rose, 2017) and personal negative religious coping that seems to lead to depression among some Orthodox Jews (Pirutinsky et al, 2011). Furthermore, both family stressors (e.g., parenting) and religious struggles seem to have substantial cross-cultural variance, increasing the need for nuanced study of related phenomena (Pirutinsky, Schechter, Kor, & Rosmarin, 2015). We explore the relational struggles experienced by highly religious families in the United States, with focused attention on families in minority faiths.…”
mentioning
confidence: 99%